Human mesenchymal stem cells–derived conditioned medium inhibits hypoxia‐induced death of neonatal porcine islets by inducing autophagy. (2nd October 2019) - Xu, Yuzhi; Tan, Mengqun; Ma, Xiaoqian; Li, Hongde; He, Xuesong; Chen, Zeyi; Tan, Yixiong; Nie, Wei; Rong, Pengfei; Wang, Wei
Abstract: Background: The dysfunction of islet grafts is generally attributed to hypoxia‐induced damage. Mesenchymal stem cells (MSCs) are currently thought to effectively protect cells from various risk factors via regulating autophagy. In our study, we investigated if human umbilical cord‐derived MSCs could ameliorate hypoxia‐induced apoptosis in porcine islets by modulating autophagy, and we explored the underlying mechanisms. Methods: Neonatal porcine islet cell clusters (NICCs) were cultured with human umbilical cord‐derived MSC conditioned medium (huc‐MSC‐CM) and RPMI‐1640 medium (control) under hypoxic conditions (1% O2 ) in vitro. NICCs were treated with 3‐methyladenine (3‐MA) and chloroquine (CQ) to examine the role of huc‐MSC‐CM in regulating autophagy. Finally, the levels of several cytokines secreted by huc‐MSCs were detected by ELISAs, and the corresponding inhibitors were applied to investigate which cytokine mediates the protective effects of huc‐MSC‐CM. The effects of huc‐MSC‐CM on NICCs viability and autophagy were examined using AO/PI staining, flow cytometry analysis, transmission electron microscopy (TEM) and confocal fluorescence microscopy analysis. The insulin secretion of NICCs was tested with an insulin immunoradiometric assay kit. Results: Compared to the control, the huc‐MSC‐CM treatment improved the viability of NICCs, inhibited apoptosis, increased autophagic activity and the levels of PI3K class III and phosphorylated Akt, while the ratio of phosphorylated mTOR/mTOR was reduced. These changes were reversed by CQ and 3‐MA treatments. High concentrations of IL‐6 were detected in hu‐MSC‐CM. Furthermore, recombinant IL‐6 pre‐treatment exerted similar effects as huc‐MSC‐CM, and these effects were reversed by a specific inhibitor of IL‐6 (Sarilumab). Conclusions: Our results demonstrated that huc‐MSC‐CM improved islet viability and function by increasing autophagy through the PI3K/Akt/mTOR pathway under hypoxic conditions. Additionally, IL‐6 plays an important role in the function of huc‐MSC‐CM.